Human autoimmunity at single cell resolution in aplastic anemia before and after effective immunotherapy - Zhijie Wu; Shouguo Gao; Xingmin Feng; Haoran Li; Nicolas Sompairac; Shirin Jamshidi; Desmond Choy; Rita Antunes Dos Reis; Qingyan Gao; Sachiko Kajigaya; Lemlem Alemu; Diego Quinones Raffo; et al. (Nature Communications)
Abstract Severe immune aplastic anemia is a fatal disease due to the destruction of marrow hematopoietic cells by cytotoxic lymphocytes, serving as a paradigm for marrow failure syndromes and autoimmune diseases. To better understand its pathophysiology, we apply advanced single cell methodologies, including mass cytometry, single-cell RNA, and TCR/BCR sequencing, to patient samples from a clinical trial of immunosuppression and growth factor stimulation. We observe opposing changes in the abundance of myeloid cells and T cells, with T cell clonal expansion dominated by effector memory cells. Therapy reduces and suppresses cytotoxic T cells, but new T cell clones emerge hindering robust hematopoietic recovery. Enhanced cell-cell interactions including between hematopoietic cells and immune cells, in particular evolving IFNG and IFNGR, are noted in patients and are suppressed post-therapy. Hematologic recovery occurs with increases in the progenitor rather than stem cells. Genetic predispositions linked to immune activation genes enhances cytotoxic T cell activity and crosstalk with target cells.